Implementation of Indonesia Language Learning in (P5) Independent Curriculum at Muhammadiyah Middle School - Klarisa, Dea; Markhamah, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research aims to describe the implementation of Indonesian language learning in the (P5) independent curriculum at Muhammadiyah Middle Schools. This research uses a qualitative descriptive approach, The author uses a descriptive approach because the method is to examine and explain the findings that have been obtained to be described. The subjects in this research were Indonesian language subject teachers. Data collection was carried out using observation, interviews, and case study techniques. Data was analyzed after inspection. The results of the examination revealed challenges, obstacles, and strategies for learning Indonesian in the Pancasila student profile of the independent curriculum. The results of this research show that: (1) There are challenges and obstacles to implementing the Pancasila student profile. The challenge is mastering learning needs in the digital era and, lack of reference sources. Meanwhile, obstacles, namely no educational experience, low interest in literacy, and inadequate facilities require a lot of estimated time to work on the project; (2) Indonesian language learning strategies in the independent curriculum. There is a division of student learning styles and Pancasila student profile projects in Indonesian language learning.